Impact of the Dakshata structured training module on healthcare professionals' knowledge and practices in intrapartum care: a study in a South Indian tertiary care institute - M., Priya; Sharmila, Vijayan; Kamatham, Vandana; R., Danasu; Babu, Thirunavukkarasu Arun; M., Rajeswari (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Despite the high rate of institutional deliveries in India, maternal and neonatal mortality rates remain concerning. The Dakshata programme was introduced to enhance the quality of maternal and newborn care through structured training for healthcare professionals. This study evaluates the effectiveness of the Dakshata structured training module on knowledge and practices regarding intrapartum care among healthcare workers in a tertiary care institute. Methods: A one-group pre test - post test design was used, involving 27 healthcare professionals. A self-developed 15-item multiple-choice questionnaire assessed knowledge, while Objective Structured Clinical Examination (OSCE) stations evaluated practical skills before and after the training intervention. Data were analyzed using IBM Software version 26, employing the Mann-Whitney U test and Spearman correlation for non-normally distributed data. Results: The intervention significantly improved knowledge scores from a median of 14.00 pre-intervention to 17.00 post-intervention (p<0.001). OSCE scores also showed substantial increases across all stations. The correlation analysis revealed a significant positive relationship between pre-test knowledge and OSCE4 performance (r=0.490, p=0.009), but no significant correlation was found between post-test knowledge and OSCE scores. Conclusions: The Dakshata structured training module effectively enhanced healthcare workers' knowledge and practical skills in intrapartum care. Continued investment in targeted training programs is essential to improve maternal and newborn care quality.